The SAGE encyclopedia of contemporary early childhood education - Couchenour, Donna L. (Donna Lee), 1950-; Chrisman, J. Kent (Thousand Oaks, California : SAGE Publications, Inc., 2016)
'The SAGE Encyclopedia of Contemporary Early Childhood Education' presents in three comprehensive volumes advanced research, accurate practical applications of research, historical foundations and key facts from the field of contemporary early childhood education.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 3, 2016).
Keywords: Early childhood education -- Encyclopedias; Child development -- Encyclopedias